How To Improve Business Performance Of Msmes In The Covid-19 Pandemic Through Knowledge Sharing - Wijaya, Andy; Sisca (Publisher Cv. Inara, 2023)
Micro, Small and Medium Enterprises (MSMEs) are economic drivers in both developed and developing countries, including Indonesia. In an effort to improve the performance of MSMEs, it is necessary to pay attention to the application of knowledge sharing within these MSMEs. The purpose of this study was to analyze the relationship between the application of the knowledge sharing model and the improvement in the performance of MSMEs especially during the Covid-19 Pandemic. The research subjects taken in this study were MSME actors in the food and beverage sector at Pematangsiantar City, totaling 374 MSMEs. The analysis technique used in this study was Structural Equation Modeling (SEM) using the Smart PLS program. The results of this study indicated that the performance of MSMEs increases when the application of knowledge sharing went well, this couldbe seen from the test results which showed that tacit knowledge sharing had a positive and significant effect on marketing performance and explicit knowledge sharing has a positive and significant effect on financial performance. However, it was different from the effect of explicit knowledge sharing on marketing performance which showed a negative and significant influence.